LITERATURE REVIEW : FAKTOR RISIKO KEKERASAN SEKSUAL PADA REMAJA - Sudaryasa, Wayan Adi; Dwiana, Nungki Agnes; Nurmalasari, Rizky Diana; Zahidah, Adelina Najla; Rahmah, Zayyinaa Aulia; Wijayanti, Siwi Pramatama Mars (VISIKES: Jurnal Kesehatan Masyarakat, 2023)
Every year sexual violence cases increase and become a widely heard issue in the community. The increase in cases that occur requires research that examines what the risk fator affects. The purpose of this study was to analyze scientific articles related to what are the risk factors for sexual violence in adolescents. The research employed literature review. The literature consists of journals with a travel year from 2017 to 2022. Literature collection was done through Google scholar, Pubmed, and ScienceDirect using the keyword “sexual violence”, “risk factor”, and “teenager”. The results of the literature search 34.927 articles found in the database regarding entered keywords; however 34.917 articles were excluded because they were not relevant to the author’s criteria. There were 10 articles that met the inclusion criteria, however only ten articles categorized as good quality. Review results show that have any risk factors affecting sexual violence of a teenager, among other things gender, alcohol, drug, age, sexual disorder, family, gadget, environmnet, disability, a poor parental education, economic, syahwat, religion, dating, and sexual intercourse.